Incorporating Cost-Effectiveness Data in a Fair Process for Priority Setting Efforts; Comment on "Use of Cost-Effectiveness Data in Priority Setting Decisions: Experiences from the National Guidelines for Heart Diseases in Sweden" - Sitaporn Youngkong (Kerman University of Medical Sciences, 2015)
Cost-effectiveness data is useful for use in priority setting decisions in order to improve the efficiency of resources used. This paper thereby responds to Eckard et al. which addressed the use of cost-effectiveness data in the actual prioritization decisions in the Swedish national clinical guidelines for heart diseases. Based on a set of experiences on the use of economic evaluation in priority setting processes, this paper emphasizes the potential approach to incorporating cost-effectiveness data in the prioritization process to enhance transparency of the decisions, and highlights the importance of designing a fair decision-making process that can enforce the sustained implementation of cost-effectiveness data.